2013
DOI: 10.1039/c3cc40434j
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous organosilica membrane for water desalination

Abstract: Nanoporous organosilica membranes are successfully coated on porous alumina tubes and tested for desalination via membrane distillation. The membranes produced pure water (up to 13 kg m(-2) h(-1)) across an extreme range of salt concentrations (10-150 g L(-1) NaCl) at moderate temperatures (≤60 °C) without exhibiting the characteristic flux decay of competing materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…As shown in Table 1, all these microporous inorganic membranes generally deliver high salt rejection at improved water fluxes of values up 11.5 kg m -2 h -1 depending upon the testing conditions. Recently, Chua and co-workers reported the preparation of ordered mesoporous silica membranes delivering reasonable water fluxes and high salt rejection [12]. A more recent work from Diniz da Costa's group [14] has shown that interlayer free carbonised template silica membranes formed mesoporous carbon moieties within the silica matrix, thus conferring improved water fluxes of up to [17,18] and ultrafiltration [19] processes only.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, all these microporous inorganic membranes generally deliver high salt rejection at improved water fluxes of values up 11.5 kg m -2 h -1 depending upon the testing conditions. Recently, Chua and co-workers reported the preparation of ordered mesoporous silica membranes delivering reasonable water fluxes and high salt rejection [12]. A more recent work from Diniz da Costa's group [14] has shown that interlayer free carbonised template silica membranes formed mesoporous carbon moieties within the silica matrix, thus conferring improved water fluxes of up to [17,18] and ultrafiltration [19] processes only.…”
Section: Introductionmentioning
confidence: 99%
“…3, are in agreement with the XRD data with all samples exhibiting long range order. For samples PMO-2-300A and PMO-2-350N this took the form of cage-like cubic pores, whereas the PMO-1-300A and PMO-1-350N samples exhibited a distorted orthogonal pore structure derived from body-centred cubic geometry [9]. This is reasonable as F127 has a longer EO chain that favours aggregation into globular structures which result in larger cage-like pores [31,32].…”
Section: Characterizationmentioning
confidence: 92%
“…pore wetting) must improve to be commercially competitive with RO has seen a new range of membrane materials emerge including ceramics [4,5] and carbon nanotubes [6], as well as different morphologies [7,8]. Of these, ordered organosilica membranes have shown considerable promise [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the water flux is sufficiently fast, the surface concentration experienced by the 0.3 and 3.5% NaCl solutions would be comparable and the real difference in vapour pressure (at the membrane surface) would be much smaller than the apparent difference (when considering the bulk liquid). A recent study into ordered mesoporous hybrid silica membranes for desalination also noted that the flux of their membranes was essentially independent of the salt feed concentration (up to 15 wt% NaCl) (Chua, Lin et al 2013). …”
Section: Analysis and Discussionmentioning
confidence: 99%